Advanced Fluid Dynamics - Woo Oh, Hyoung (IntechOpen, 2012)
This book provides a broad range of topics on fluid dynamics for advanced scientists and professional researchers. The text helps readers develop their own skills to analyze fluid dynamics phenomena encountered in professional engineering by reviewing diverse informative chapters herein.